High-performance n-type bismuth telluride-based thermoelectric material and preparation method thereof
Patent Information
- Application Number
- CN202610948863.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-27
AI Technical Summary
此发明通过碲、硒组分的调节以改善带隙,但这种对棒料直接挤压成型工艺存在机械强度不足的缺陷,难以实现高端应用
1.本发明n型碲化铋基热电材料化学式为Bi2+xTe2.7+ySe0.3-y,其中0.001<x≤0.2,-0.2≤y≤0.3,Bi组分掺杂不仅可以平衡晶粒细化和氧缺陷诱导的类施主效应,从而调控体系的载流子浓度。此外,通过掺杂还可以在晶界处形成第二相或纳米团簇等,在优化体系载流子浓度的同时还可以降低热导率,使得材料的zT值得到显著提升。此外,本发明所述的标准n型Bi2Te2.7Se0.3碲化铋基热电材料无需掺杂额外元素,只需本征掺杂便可实现热电性能的调控,且性能稳定,充分保证了热电材料热电性能的均匀性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermoelectric materials technology, and in particular to a high-performance n-type bismuth telluride-based thermoelectric material and its preparation method. Background Technology
[0002] Against the backdrop of the increasingly severe energy crisis and environmental problems, thermoelectric technology, due to its ability to directly convert heat energy into electrical energy, has become a sustainable and zero-emission solution, attracting global attention. The thermoelectric properties of thermoelectric materials can be expressed as zT=S²σT / (κ e +κ l Quantitative characterization is required, and optimization necessitates the synergistic control of high Seebeck coefficient (S), high electrical conductivity (σ), and low thermal conductivity (κ). However, intrinsic correlations exist among these three parameters: electrical conductivity (σ) and electronic thermal conductivity (κ). e The positive correlation between σ and S indicates that while increasing carrier concentration can improve σ, it suppresses S, leading to a mutual constraint in parameter optimization. This is the core challenge limiting the performance improvement of bismuth telluride-based thermoelectric materials. Besides thermoelectric properties, high mechanical properties are also crucial for the high-end applications of thermoelectric materials.
[0003] Currently, bismuth telluride-based thermoelectric materials are the most widely used thermoelectric materials in the industrial field. Commercially available bismuth telluride-based materials are mostly prepared using zone melting processes. While their high orientation allows for high zT values, their layered structure bound by van der Waals forces significantly degrades mechanical properties, hindering downstream material processing. Therefore, for the thermoelectric cooling requirements of high heat flux systems, especially the thermomechanical stress problems caused by temperature gradients, which severely restrict device reliability, there is an urgent need to develop bismuth telluride-based thermoelectric materials that combine high zT values with high mechanical strength.
[0004] Because tellurium and selenium in n-type bismuth telluride-based compounds exhibit selectivity for different anion sites, and because oxygen-vacancy-induced donor-like effects significantly deteriorate the thermoelectric performance of the n-type bismuth telluride system, complex electronic structure variations and narrow processing windows occur in n-type bismuth telluride-based compounds. Furthermore, the electrical and thermal conductivity in n-type bismuth telluride-based compounds differ significantly in the ab plane and along the c-axis, making traditional powder metallurgy strategies unfavorable for improving the performance of n-type bismuth telluride-based thermoelectric materials. This severely limits the application of high-end thermoelectric devices.
[0005] In recent years, researchers have optimized the thermoelectric performance of n-type bismuth telluride-based thermoelectric materials by introducing additional elements to adjust the band gap. For example, Li Di (application publication number CN 115884654 A) incorporated Ag₂Se powder into n-type bismuth telluride thermoelectric materials, achieving a zT of 0.85 at 350 K. Song Qingfeng (application publication number CN 118373690 A) introduced La into n-type bismuth telluride thermoelectric materials to optimize thermoelectric performance, achieving an average zT of approximately 0.87 between 300 K and 400 K. On the one hand, the additional introduction of precious elements such as Ag and La significantly increases costs; on the other hand, mixing more elements makes it difficult to guarantee uniform element distribution and stable thermoelectric performance during continuous production. Furthermore, Fan Xi'an (application publication number CN 110002412 A) improved thermoelectric performance by optimizing grain orientation through a strategy of direct extrusion molding of molten rods. This invention improves the band gap by adjusting the tellurium and selenium composition, but this direct extrusion molding process for rods suffers from insufficient mechanical strength, making it difficult to achieve high-end applications. Therefore, there is an urgent need to develop an n-type bismuth telluride-based thermoelectric material that is intrinsically doped and possesses both high zT value and high mechanical strength. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high-performance n-type bismuth telluride-based thermoelectric material and its preparation method. The method is simple and has good repeatability, and the obtained n-type bismuth telluride-based thermoelectric material has high thermoelectric performance and high mechanical properties.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing an n-type bismuth telluride-based thermoelectric material, comprising the following steps: Step 1: According to Bi 2+x Te 2.7+y Se 0.3-y According to the stoichiometric ratio, Bi, Te, and Se raw materials were weighed, added to a container, vacuumed, and then the container was placed in a swaying melting furnace for melting. After cooling, an alloy ingot was obtained; wherein, 0.001 <x≤0.2,-0.2≤y≤0.3; Step 2: The alloy ingot is ball-milled to obtain powder; Step 3: Hot-press the powder to obtain a blank; Step 4: The blank is subjected to a first annealing, and after cooling, it is subjected to hot extrusion deformation to obtain a bar stock; the bar stock is subjected to a second annealing, and after cooling, the n-type bismuth telluride-based thermoelectric material is obtained.
[0008] This invention employs an intrinsic Bi doping strategy to balance the oxygen defects and Te vacancy-induced donor-like effects in n-type bismuth telluride-based thermoelectric materials. Furthermore, it forms nanoclusters or a second phase at grain boundaries to synergistically optimize the carrier concentration and phonon transport behavior of the n-type bismuth telluride-based thermoelectric materials, thereby significantly improving their thermoelectric performance. Simultaneously, a multi-annealing process is incorporated to significantly enhance the mechanical properties of the n-type bismuth telluride-based thermoelectric materials and optimize their thermoelectric performance.
[0009] For example, in step 1, x can be any value or a range of any values, such as 0.001, 0.01, 0.05, 0.1, 0.15, or 0.2; in step 1, y can be any value or a range of any values, such as -0.2, -0.1, 0, 0.1, or 0.3.
[0010] In a preferred embodiment of the first aspect, in step 1, 0.01≤x≤0.1 and 0≤y≤0.2.
[0011] For example, in step 1, x can be any value or a range of any values, such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1; and in step 1, y can be any value or a range of any values, such as 0, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, or 0.2.
[0012] When y=0, the n-type bismuth telluride-based thermoelectric material is the standard n-type Bi₂Te. 2.7 Se 0.3 Experiments have shown that increasing the Bi doping amount makes the standard n-type Bi₂Te₅ more effective. 2.7 Se 0.3 The thermoelectric performance is significantly improved (Examples 4-7). When -0.2≤y≤0.3 and y≠0, the n-type bismuth telluride-based thermoelectric material is a non-standard n-type Bi2Te. 2.7 Se 0.3 For example: Bi2Te 2.85 Se 0.15 Experiments have shown that by increasing the Bi doping amount, a chemical formula Bi0 can be obtained. 2.06 Te 2.85 Se 0.15 The bismuth telluride-based thermoelectric material showed significantly improved thermoelectric performance (Example 8). This demonstrates that the intrinsic doping strategy of the Bi component in this invention is applicable to various types of n-type bismuth telluride-based thermoelectric materials.
[0013] In a preferred embodiment of the first aspect, the vacuum degree in step 1 is ≤5×10⁻⁶. -4 Pa.
[0014] In a preferred embodiment of the first aspect, the melting temperature in step 1 is 500~1000℃, the melting holding time is 2~20h, the melting heating rate is 1~10℃ / min, and the swing angle of the swing melting furnace is 30°~70°. To ensure sufficient melting of the raw materials, the present invention sets the swing angle of the swing melting furnace to 30°~70°. An angle less than 30° is unfavorable for flow, while an angle greater than 70° restricts the equipment's circuitry.
[0015] In a preferred embodiment of the first aspect, the ball milling speed in step 2 is 200~600 r / min, and the ball milling time is 1~30 h.
[0016] In a preferred embodiment of the first aspect, step 2 further includes sieving the powder to obtain a particle size ≤100 mesh. Excessively coarse particle size is detrimental to mechanical properties, while excessively fine particle size introduces more oxygen defects, which is detrimental to thermoelectric properties. Therefore, considering stability, thermoelectric properties, mechanical properties, and raw material utilization, this invention selects powder with a particle size ≤100 mesh.
[0017] In a preferred embodiment of the first aspect, the hot pressing temperature in step 3 is 400~500℃, the heating rate is 12~15℃ / min, the pressing pressure is 20~250MPa, and the rate of change of the pressing pressure is 1~10MPa / min.
[0018] In a preferred embodiment of the first aspect, the temperature of the first annealing in step 4 is 300~500℃, and the annealing time is 1~48h.
[0019] As a preferred embodiment of the first aspect, the mold used for hot extrusion in step 4 includes, but is not limited to, an integral molding mold, a two-part molding mold, and a four-part molding mold.
[0020] In a preferred embodiment of the first aspect, the hot deformation temperature in the hot extrusion of step 4 is 400~500℃, the heating rate is 1~2℃ / min, and the hot deformation rate is 0.005~1mm / s; preferably, the hot deformation rate is 0.005~0.2mm / s.
[0021] As a preferred embodiment of the first aspect, the deformation ratio of the hot extrusion deformation in step 4 is (4~24):1. For example, the deformation ratio is any value or any range of 4:1, 6:1, 8:1, 10:1, 12:1, 16:1, 20:1 or 24:1.
[0022] In a preferred embodiment of the first aspect, the temperature of the second annealing in step 4 is 360~500℃, and the annealing time is 6~148h.
[0023] In a second aspect, the present invention provides an n-type bismuth telluride-based thermoelectric material prepared by the method described in the first aspect, wherein the chemical formula of the material is Bi. 2+x Te 2.7+y Se 0.3-y , of which 0.001 <x≤0.2,-0.2≤y≤0.3。
[0024] This invention is based on standard n-type Bi2Te 2.7 Se 0.3 By increasing the Bi content in bismuth telluride-based thermoelectric materials, the donor-like effect induced by oxygen defects and Te vacancies can be balanced by regulating the Bi content. Nanoclusters or a second phase can be formed at grain boundaries to synergistically optimize the carrier concentration and phonon transport behavior of n-type bismuth telluride-based thermoelectric materials, thereby significantly improving the thermoelectric performance of n-type bismuth telluride-based thermoelectric materials.
[0025] This invention utilizes an intrinsic Bi doping strategy to balance the donor-like effect induced by oxygen defects and Te vacancies, thereby improving the thermoelectric performance of bismuth telluride-based thermoelectric materials containing other proportions of Te and Se. Example 8 (Bi 2.06 Te 2.85 Se 0.15 When Te and Se are in other ratios (non-standard n-type Bi2Te) 2.7 Se 0.3 When adjusting the Bi composition, the performance of bismuth telluride-based thermoelectric materials can be improved, demonstrating the universality of the Bi composition doping control method of this invention.
[0026] In a preferred embodiment of the second aspect, 0.01 ≤ x ≤ 0.1, 0 ≤ y ≤ 0.2. Through optimization, this invention limits the values of x and y to this range, resulting in a zT value for the n-type bismuth telluride-based thermoelectric material in the range of 0.85 to 1.0, thus giving it better thermoelectric performance.
[0027] As a preferred embodiment of the second aspect, the n-type bismuth telluride-based thermoelectric material satisfies any one of the following: (1) The Seebeck coefficient at 300K is -180 to -240 μV / K; (2) The conductivity at 300K is 0.7×10 5 ~1.2×10 5 S / m; (3) The thermal conductivity at 300K is 1.0~1.8W / m / K: (4) The thermoelectric figure of merit zT at 300K is 0.85~1.0; (5) Compressive strength ≥190MPa.
[0028] Tests show that, with the preparation process of the present invention and the Bi regulation strategy, the n-type bismuth telluride-based thermoelectric material of the present invention has the aforementioned high thermoelectric properties and high mechanical properties.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The chemical formula of the n-type bismuth telluride-based thermoelectric material of the present invention is Bi 2+x Te 2.7+y Se 0.3-y , where 0.001<x≤0.2, -0.2≤y≤0.3. Bi component doping can not only balance grain refinement and the donor-like effect induced by oxygen defects, so as to regulate the carrier concentration of the system. In addition, the doping can also form a second phase or nanoclusters at grain boundaries, which can reduce the thermal conductivity while optimizing the carrier concentration of the system, so that the zT value of the material is significantly improved. Furthermore, the standard n-type Bi2Te 2.7 Se 0.3 bismuth telluride-based thermoelectric material of the present invention does not need to be doped with additional elements, and the regulation of thermoelectric properties can be realized only through intrinsic doping, with stable performance, which fully ensures the uniformity of the thermoelectric properties of the thermoelectric material.
[0030] 2. The preparation method provided by the present invention undergoes multiple annealing processes and deformation processes, with a compressive strength of up to 190 MPa or more, uniform and stable mechanical properties, which is beneficial to industrial large-scale production and application. Detailed Description of the Embodiments
[0031] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in combination with specific embodiments.
[0032] Embodiment 1 The chemical formula of the n-type bismuth telluride-based thermoelectric material in this embodiment is Bi2Te 2.7 Se 0.3 (standard n-type Bi2Te 2.7 Se 0.3 bismuth telluride-based thermoelectric material), and the preparation method thereof includes the following steps: Step 1: According to the stoichiometric ratio of the chemical formula Bi2Te 2.7 Se 0.3 , weigh the Bi, Te and Se simple substances each with a purity of 99.99% or above, mix them uniformly, load the mixture into a quartz tube, and carry out vacuum sealing with a vacuum degree of 5×10 -4 Pa; then, transfer the quartz tube to a rocking muffle furnace for melting, first heat up to 700°C at a rate of 5°C / min, hold the temperature for 4 h, set the rocking angle of the rocking melting furnace to 45°, and cool the mixture along with the furnace to obtain an alloy ingot; Step 2: After crushing the alloy ingot obtained in Step 1, it is placed into a stainless steel ball mill jar for ball milling; the ball milling speed is 450 r / min and the ball milling time is 16 h to obtain powder; the powder is then sieved through a 100-mesh sieve to obtain uniform and fine powder. Step 3: The powder obtained in Step 2 is loaded into a cylindrical stainless steel mold for hot pressing. The hot pressing temperature is 460℃, the heating rate is 10℃ / min, the pressing pressure is 100MPa, and the pressing pressure change rate is 5MPa / min. Finally, a dense circular block blank is obtained. Step 4: Anneal the block blank obtained in Step 3 in an oven at 400℃ for 8 hours and then cool it in the furnace (i.e., the first annealing); then put it into a four-lobed hot extrusion mold for hot extrusion deformation. The hot deformation temperature is 460℃, the heating rate is 1℃ / min, the hot deformation rate is 0.01mm / s, and the deformation ratio is 10:1 to obtain a long cylindrical bar; then place the bar in an oven at 400℃ for annealing for 144 hours and then cool it in the furnace (i.e., the second annealing) to obtain the n-type bismuth telluride thermoelectric material.
[0033] Example 2 The only difference between Example 2 and Example 1 is the parameters used in the preparation method. The specific preparation method includes the following steps: The chemical formula of the n-type bismuth telluride-based thermoelectric material in this embodiment is Bi₂Te. 2.7 Se 0.3 (Standard n-type Bi2Te) 2.7 Se 0.3 The preparation method of bismuth telluride-based thermoelectric materials includes the following steps: Step 1: According to the chemical formula Bi2Te 2.7 Se 0.3 According to the stoichiometric ratio, Bi, Te, and Se elements with a purity of ≥99.99% were weighed out, mixed thoroughly, and then placed into a quartz tube. The tube was then vacuum-sealed at a vacuum level of 5 × 10⁻⁶. -4 Pa; then, the quartz tube was transferred to a swing muffle furnace for melting. The temperature was first raised to 500°C at a rate of 1°C / min and held for 20 hours. The swing angle of the swing melting furnace was 30°. After cooling with the furnace, the alloy ingot was obtained. Step 2: After crushing the alloy ingot obtained in Step 1, put it into a stainless steel ball mill jar for ball milling; the ball milling speed is 200 r / min and the ball milling time is 30 h to obtain powder; after sieving the powder through a 100 mesh sieve, uniform and fine powder is obtained. Step 3: The powder obtained in Step 2 is loaded into a cylindrical stainless steel mold for hot pressing. The hot pressing temperature is 400℃, the heating rate is 12℃ / min, the pressing pressure is 20MPa, and the pressing pressure change rate is 1MPa / min. Finally, a dense circular block blank is obtained. Step 4: Anneal the block blank obtained in Step 3 in a 300℃ oven for 48 hours and then cool it in the furnace (i.e., the first annealing); then put it into a four-lobed hot extrusion die for hot extrusion deformation. The hot deformation temperature is 400℃, the heating rate is 1℃ / min, the hot deformation rate is 0.005mm / s, and the deformation ratio is 4:1 to obtain a long cylindrical bar; then place the bar in a 360℃ oven for annealing for 148 hours and then cool it in the furnace (i.e., the second annealing) to obtain the n-type bismuth telluride thermoelectric material.
[0034] Example 3 The only difference between Example 3 and Example 1 is the parameters used in the preparation method. The specific preparation method includes the following steps: The chemical formula of the n-type bismuth telluride-based thermoelectric material in this embodiment is Bi₂Te. 2.7 Se 0.3 (Standard n-type Bi2Te) 2.7 Se 0.3 The preparation method of bismuth telluride-based thermoelectric materials includes the following steps: Step 1: According to the chemical formula Bi2Te 2.7 Se 0.3 According to the stoichiometric ratio, Bi, Te, and Se elements with a purity of ≥99.99% were weighed out, mixed thoroughly, and then placed into a quartz tube. The tube was then vacuum-sealed at a vacuum level of 5 × 10⁻⁶. -4 Pa; then, the quartz tube was transferred to a swing muffle furnace for melting. The temperature was first raised to 1000℃ at a rate of 10℃ / min and held for 20h. The swing angle of the swing melting furnace was 70°. After cooling with the furnace, the alloy ingot was obtained. Step 2: After crushing the alloy ingot obtained in Step 1, put it into a stainless steel ball mill jar for ball milling; the ball milling speed is 600 r / min and the ball milling time is 1 h to obtain powder; after sieving the powder through a 100-mesh sieve, uniform and fine powder is obtained. Step 3: The powder obtained in Step 2 is loaded into a cylindrical stainless steel mold for hot pressing. The hot pressing temperature is 500℃, the heating rate is 15℃ / min, the pressing pressure is 250MPa, and the pressing pressure change rate is 10MPa / min. Finally, a dense circular block blank is obtained. Step 4: Anneal the block blank obtained in Step 3 in a 500℃ oven for 1 hour and then cool it in the furnace (i.e., the first annealing); then put it into a four-lobed hot extrusion die for hot extrusion deformation. The hot deformation temperature is 500℃, the heating rate is 2℃ / min, the hot deformation rate is 1mm / s, and the deformation ratio is 21:1 to obtain a long cylindrical bar; then place the bar in a 500℃ oven for annealing for 148 hours and then cool it in the furnace (i.e., the second annealing) to obtain the n-type bismuth telluride thermoelectric material.
[0035] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the block blank was not annealed in step 4 (i.e., the first annealing was missing). The rest is the same as in Example 1. Step 4 is as follows: Step 4: The block blank obtained in Step 3 is directly loaded into a four-lobed hot extrusion mold for hot extrusion deformation. The deformation ratio is 10:1, the hot deformation temperature is 460℃, and the extrusion speed is 0.01mm / s to obtain a long cylindrical bar. Then, the bar is placed in a 400℃ oven for annealing for 144h and then cooled in the furnace to obtain the n-type bismuth telluride thermoelectric material.
[0036] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the extruded bar stock was not annealed in step 4 (i.e., a second annealing was missing). The rest is the same as in Example 1. Step 4 is as follows: Step 4: Anneal the block blank obtained in Step 3 in an oven at 400℃ for 8 hours and then cool it in the furnace; then put it into a four-lobed hot extrusion mold for hot extrusion deformation. The hot deformation temperature is 460℃, the heating rate is 1℃ / min, the hot deformation rate is 0.01mm / s, and the deformation ratio is 10:1 to obtain a long cylindrical bar, which is the n-type bismuth telluride thermoelectric material.
[0037] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that annealing is not performed in step 4 (i.e., two annealing processes are missing). The rest is the same as in Example 1. Step 4 is as follows: Step 4: The block blank obtained in Step 3 is directly loaded into a four-lobed hot extrusion mold for hot extrusion deformation. The hot deformation temperature is 460℃, the heating rate is 1℃ / min, the hot deformation rate is 0.01mm / s, and the deformation ratio is 10:1 to obtain a long cylindrical bar, which is the n-type bismuth telluride thermoelectric material.
[0038] Example 4 The only difference between Example 4 and Example 1 is that the chemical formula of the n-type bismuth telluride-based thermoelectric material is Bi. 2.01 e 2.7 Se 0.3 The rest is the same as in Example 1.
[0039] Example 5 The only difference between Example 5 and Example 1 is that the chemical formula of the n-type bismuth telluride-based thermoelectric material is Bi. 2.05 Te 2.7 Se 0.3 The rest is the same as in Example 1.
[0040] Example 6 The only difference between Example 6 and Example 1 is that the chemical formula of the n-type bismuth telluride-based thermoelectric material is Bi. 2.1 Te 2.7 Se 0.3 The rest is the same as in Example 1.
[0041] Example 7 The only difference between Example 7 and Example 1 is that the chemical formula of the n-type bismuth telluride-based thermoelectric material is Bi. 2.2 Te 2.7 Se 0.3 The rest is the same as in Example 1.
[0042] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the chemical formula of the n-type bismuth telluride-based thermoelectric material is Bi. 2.3 Te 2.7 Se 0.3 The rest is the same as in Example 1.
[0043] Example 8 The only difference between Example 8 and Example 1 is that the chemical formula of the n-type bismuth telluride-based thermoelectric material is Bi. 2.08 Te 2.85 Se 0.15 The rest is the same as in Example 1.
[0044] Comparative Example 5 The only difference between Comparative Example 5 and Example 1 is that the chemical formula of the n-type bismuth telluride-based thermoelectric material is Bi. 2.3 Te 2.85 Se 0.15 The rest is the same as in Example 1.
[0045] Test case 1. Testing method: The n-type bismuth telluride-based materials obtained in the above examples and comparative examples were cut to specific dimensions required for testing, and the test surfaces were polished with 4000-grit sandpaper. Due to thermal deformation, bismuth telluride-based thermoelectric materials have better texture and thermoelectric properties parallel to the extrusion direction; therefore, the cutting and testing orientation of the samples were both parallel to the extrusion direction.
[0046] The compressive strength of the samples was tested using a universal testing machine. The electrical conductivity (σ) and Seebeck coefficient (S) of the thermoelectric material at 300K were measured using a CTA thermoelectric testing system. The thermal conductivity (κ) of the samples was tested using a CLA laser thermal conductivity meter. The power factor (PF) and thermoelectric figure of merit (zT) of the thermoelectric material were calculated using the formulas PF=S²σ and zT=S²σT / κ.
[0047] 2. Test Results: Table 1: Test Results of Various Indicators at 300K The test results are shown in Table 1. A comparison of Comparative Examples 1-3 and Examples 1-3 shows that the introduction of a secondary annealing process for both the billet and the ingot significantly improves the mechanical properties. In Comparative Example 3, the unannealed billet was directly hot-extruded without secondary annealing, resulting in an ingot compressive strength of only 96 MPa, lower than the compressive strength of the ingot after only a second annealing (Comparative Example 1, 116 MPa). In Comparative Example 2, the annealed billet was hot-extruded, but the extruded ingot did not undergo secondary annealing, resulting in an ingot compressive strength of only 147 MPa, significantly lower than the compressive strength of the ingot obtained in Example 1 through a single billet annealing and a second ingot annealing (Example 1, 175 MPa). This is because annealing of the billet not only helps to release the processing stress during the powder pressing deformation process, but also helps to improve the machinability of bismuth telluride materials and reduce the risk of cracking during hot extrusion; while the introduction of the crystal rod annealing process can not only release the stress during the hot deformation process of the crystal rod, but also promote grain recrystallization, refine the grains, and further improve the mechanical properties of the crystal rod.
[0048] Meanwhile, as can be seen from Table 1, the secondary annealing process of Examples 1-3 can also optimize the standard n-type Bi2Te 2.7 Se 0.3 The thermoelectric performance is improved compared to the power factor and zT value of Comparative Examples 1-3.
[0049] Other test results are shown in Table 1. Example 1 exhibits extremely high room temperature conductivity (2.13 × 10⁻⁶). 5 S m -1 High room temperature thermal conductivity (room temperature thermal conductivity reaches 2.01 W / m²) -1 K -1 ) and a moderate power factor (36.63 μW cm⁻¹) -1 K -2 This results in an extremely low zT value (only 0.56 at room temperature). The ultra-high electrical and thermal conductivity can be attributed to the donor-like effect induced by oxygen vacancies and thermal deformation processes, leading to an excessively high carrier concentration in the system, thus resulting in high electrical and electronic thermal conductivity. Therefore, in order to further improve the standard n-type Bi₂Te2.7 Se 0.3 The thermoelectric properties of bismuth telluride-based thermoelectric materials: This invention employs an intrinsic Bi doping strategy to balance the standard n-type Bi₂Te composition. 2.7 Se 0.3 The oxygen defects and Te vacancies induce a donor-like effect, thereby significantly improving the thermoelectric performance of n-type bismuth telluride-based thermoelectric materials.
[0050] As can be seen from Table 1, Examples 4-7 and Comparative Example 4 were doped with Bi component based on Example 1. In Example 4, the thermal conductivity of the material decreased to 1.78 W / m². -1 K -1 The conductivity is 1.86 × 10⁻⁶. 5 S m -1 The Seebeck coefficient is -140.03 μV / K, and the power factor reaches 36.46 μW cm⁻¹. -1 K -2 The room temperature zT value increased to 0.63, a 12.5% increase compared to Example 1. In Example 5, the thermal conductivity of the material decreased to 1.30 W / m. -1 K -1 The conductivity is 1.03 × 10⁻⁶. 5 S m -1 The Seebeck coefficient is -202.88 μV / K, and the power factor is as high as 42.43 μW / cm. -1 K -2 The room temperature zT value increased to 0.98, a 75% increase compared to Example 1. In Example 6, the thermal conductivity of the material decreased to 1.25 W / m². -1 K -1 The conductivity is 0.85 × 10⁻⁶. 5 S m -1 The Seebeck coefficient is -217.00 μV / K, and the power factor reaches 40.04 μW / cm. -1 K -2 The room temperature zT value increased to 0.96, a 71.4% increase compared to Example 1. In Example 7, the thermal conductivity of the material decreased to 1.22 W / m². -1 K -1 The conductivity is 0.55 × 10⁻⁶. 5 S m -1 The Seebeck coefficient is -245.61 μV / K, and the power factor is 37.94 μW / cm. -1 K -2 The room temperature zT value increased to 0.82, which is 46.4% higher than the zT value in Example 1.
[0051] In Comparative Example 4, the thermal conductivity of the material decreased to 1.18 W / m². -1 K-1 , the electrical conductivity is 0.32×10 5 S m -1 , the Seebeck coefficient is -258.86μV / K, and the power factor is only 21.44μW cm -1 K -2 , and the zT value at room temperature is 0.55, which is still insufficient compared with Example 1. It can be seen that the effect is poor beyond the scope defined by the present invention. Therefore, the present invention limits the Bi doping range to 0.001<x≤0.2, the preferred range is 0.01≤x≤0.1, and the optimal value is 0.05.
[0052] In the present invention, grain refinement is balanced with the donor-like effect induced by oxygen defects and tellurium vacancy defects through Bi component doping regulation. It is found that for different ratios of Te and Se, high thermoelectric performance can also be achieved by optimizing the Bi component content. In Example 8, by simultaneously adjusting the relative contents of the three components Bi, Te and Se, the power factor is as high as 41.12μWcm -1 K -2 , and the zT value at room temperature is 0.95. This demonstrates the universality of Bi component doping regulation. It is worth noting that excessively high doping content will also lead to too low carrier concentration of the system, which is not conducive to achieving a high power factor. As shown in Comparative Example 5, the electrical conductivity is only 0.33×10 5 S m -1 , and the power factor is as low as 29μW cm -1 K -2 , and the zT value is also significantly reduced to only 0.72.
[0053] Component doping not only affects the thermoelectric performance, but also significantly improves the mechanical properties of the thermoelectric crystal ingot. As shown in Table 1, compared with Example 1, after the grain boundary strengthening introduced by Bi component regulation in Examples 4-7, the compressive strength of the crystal ingots is significantly improved. In particular, Example 5 has a compressive strength as high as 201MPa, which is 14.8% higher than that of Example 1 (175MPa). This excellent mechanical property is extremely beneficial for the subsequent cutting and processing of small-sized crystal grains (such as <0.2 mm×0.2 mm).
[0054] Finally, it should be noted that the above examples are only used to illustrate the technical solution of the present invention rather than limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred examples, those of ordinary skill in the art should understand that modifications or equivalent substitutions can be made to the technical solution of the present invention without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an n-type bismuth telluride-based thermoelectric material, characterized in that, The method includes the following steps: Step 1: According to Bi 2+x Te 2.7+y Se 0.3-y According to the stoichiometric ratio, Bi, Te, and Se raw materials were weighed, added to a container, vacuumed, and then the container was placed in a swaying melting furnace for melting. After cooling, an alloy ingot was obtained; wherein, 0.001 <x≤0.2,-0.2≤y≤0.3; Step 2: The alloy ingot is ball-milled to obtain powder; Step 3: Hot-press the powder to obtain a blank; Step 4: The blank is subjected to a first annealing, and after cooling, it is subjected to hot extrusion deformation to obtain a bar stock; the bar stock is subjected to a second annealing, and after cooling, the n-type bismuth telluride-based thermoelectric material is obtained.
2. The preparation method according to claim 1, characterized in that, In step 1, 0.01 ≤ x ≤ 0.1 and 0 ≤ y ≤ 0.
2.
3. The preparation method according to claim 1, characterized in that, In step 1, the melting temperature is 500~1000℃, the melting holding time is 2~20h, the melting heating rate is 1~10℃ / min, and the swing angle of the swing melting furnace is 30°~70°.
4. The preparation method according to claim 1, characterized in that, In step 3, the hot pressing temperature is 400~500℃, the heating rate is 12~15℃ / min, the pressing pressure is 20~250MPa, and the rate of change of the pressing pressure is 1~10MPa / min.
5. The preparation method according to claim 1, characterized in that, The temperature of the first annealing in step 4 is 300~500℃, and the annealing time is 1~48h.
6. The preparation method according to claim 1, characterized in that, The hot extrusion temperature in step 4 is 400~500℃, the heating rate is 1~2℃ / min, and the hot extrusion rate is 0.005~1mm / s.
7. The preparation method according to claim 1, characterized in that, The temperature of the second annealing in step 4 is 360~500℃, and the annealing time is 6~148h.
8. An n-type bismuth telluride-based thermoelectric material prepared by the preparation method according to any one of claims 1 to 7, characterized in that, The chemical formula of the material is Bi. 2+x Te 2.7+y Se 0.3-y , of which 0.001 <x≤0.2,-0.2≤y≤0.3。 9. The n-type bismuth telluride-based thermoelectric material as described in claim 8, characterized in that, 0.01≤x≤0.1, 0≤y≤0.
2.
10. The n-type bismuth telluride-based thermoelectric material as described in claim 8, characterized in that, Satisfy any of the following: (1) The Seebeck coefficient at 300K is -180 to -240 μV / K; (2) The conductivity at 300K is 0.7×10 5 ~1.2×10 5 S / m; (3) The thermal conductivity at 300K is 1.0~1.8W / m / K: (4) The thermoelectric figure of merit zT at 300K is 0.85~1.0; (5) Compressive strength ≥190MPa.
Citation Information
Patent Citations
Preparation method of preferentially oriented n-type bismuth telluride-based polycrystalline bulk thermoelectric material
CN110002412A
High-performance n-type bismuth telluride-based thermoelectric material and preparation method thereof
CN115884654A
N-type bismuth telluride-based thermoelectric material and preparation method thereof
CN118373690A